Mapping the Distributions of Exoplanet Populations with NICI and GPI. Issue Volume 10:Issue S314(2015) (November 2015) - Nielsen, Eric L.; Liu, Michael C.; Wahhaj, Zahed; Biller, Beth A.; Hayward, Thomas L.; Close, Laird M.; Macintosh, Bruce; Savransky, Dmitry; Wang, Jason J.; Graham, James R.; De Rosa, Robert J.; et al.
Abstract: While more and more long-period giant planets are discovered by direct imaging, the distribution of planets at these separations (≳5 AU) has remained largely uncertain, especially compared to planets in the inner regions of solar systems probed by RV and transit techniques. The low frequency, the detection challenges, and heterogeneous samples make determining the mass and orbit distributions of directly imaged planets at the end of a survey difficult. By utilizing Monte Carlo methods that incorporate the age, distance, and spectral type of each target, we can use all stars in the survey, not just those with detected planets, to learn about the underlying population. We have produced upper limits and direct measurements of the frequency of these planets with the most recent generation of direct imaging surveys. The Gemini NICI Planet-Finding Campaign observed 220 young, nearby stars at a median H-band contrast of 14.5 magnitudes at 1", representing the largest, deepest search for exoplanets by the completion of the survey. The Gemini Planet Imager Exoplanet Survey is in the process of surveying 600 stars, pushing these contrasts to a few tenths of an arcsecond from the star. With the advent of large surveys (many hundreds of stars) using advanced planet-imagers we gain the ability to move beyond measuring the frequency of wide-separation giant planets and to simultaneously determine the distribution as a function of planet mass, semi-major axis, and stellar mass, and so directly test models of planet formation and evolution.